2017
DOI: 10.1186/s12913-017-2555-y
|View full text |Cite
|
Sign up to set email alerts
|

Perception and attitude of Korean physicians towards generic drugs

Abstract: BackgroundIn 2012, a new pharmaceutical policy was introduced in Korea. According to the new policy, off-patent brand-name drugs (original drugs) and generic drugs must be priced the same.MethodsThis study aims to investigate the perception and attitude of Korean physicians towards generic drugs before and after the policy reform. Surveys were conducted with registered doctors at the Health Insurance Review Agency (HIRA) twice, in 2011 and 2013, by means of email and HIRA online survey systems.ResultsIn the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…The standard for BE studies in South Korea has been comprehensively reformed since 2006 to be at par with the global standards ( Ryu and Kim, 2017 ). However, specific regulatory requirements are either absent or different from those of other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The standard for BE studies in South Korea has been comprehensively reformed since 2006 to be at par with the global standards ( Ryu and Kim, 2017 ). However, specific regulatory requirements are either absent or different from those of other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Since the opinions on ensuring safety measures and guaranteeing the quality of generic drugs compared to their original counterparts were also very positive, higher confidence in the processes of approval of medicinal products on the Czech market can be expected. Similarly, positive opinions have been reported in studies conducted in developed countries, where transparent, clear, and effective regulatory rules for generic substitution had been set up [27, 28]. On the other hand, healthcare professionals from countries with a less mature healthcare system appeared to have more concerned about the manufacturing sources of generics [20, 29, 30].…”
Section: Discussionmentioning
confidence: 81%
“…From the associations of socio-demographic characteristics, positive opinions on bioequivalence can be highlighted in ambulatory physicians, who are presumably more apt to prescribe drugs with higher benevolence than in physicians in the inpatient setting. The restrictions imposed by the hospital positive lists and the influence of pharmaceutical companies may also lead to lower willingness to prescribe generics [27]. However, the associations of individual results with sociodemographic characteristics should be generally considered with caution and confirmed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, because generic drugs can be approved by confirming their bioequivalence without undergoing clinical trials, whether their clinical effects are equivalent to those of the original drug when administered in clinical settings remains controversial [ 6 , 7 ]. In a systematic review and meta-analysis comparing the safety and efficacy of original and generic cardiovascular drugs in 30 randomized controlled trials and 42 non-randomized clinical trials or observational studies, 60% of the studies identified no difference in effectiveness between original and generic administration, 26% found the original to be more efficacious and safer than the generic version, and 1% found the generic to be more effective than the original drug [ 8 ].…”
Section: Introductionmentioning
confidence: 99%